Advanced machining and finishing - Gupta, Kapil; Pramanik, Alokesh (Handbooks in Advanced Manufacturing., 2021)
Advanced Machining and Finishing explains the background theory, working principles, technical specifications, and latest developments in a wide range of advanced machining and finishing techniques. The book includes valuable technical information, tables of data, and diagrams to assist machinists. Drawing on the work of experts in both academia and industry, coverage addresses theoretical developments as well as practical improvements from R&D. With over 25 important processes, from electro-chemical machining to nano-machining and magnetic field assisted finishing, this is the most complete guide to this subject available. This unique guide will allow readers to compare the characteristics of different processes, understand how they work, and provide parameters for their effective implementation. This is part of a 4 volume set entitled Handbooks in Advanced Manufacturing, with the other 3 addressing Advanced Welding and Deforming, Additive Manufacturing and Surface Treatment, and Sustainable Manufacturing Processes.- Resumé vydavatel